Studi Perancangan Pabrik Industri Baterai Di Luwu Timur yang Mengimplementasikan Estetika, Fungsional dan Efisien - M. Febri Ardiansah; Haryanto Andi Halim (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Indonesia has abundant natural resources, one of which is nickel, which is known as an important raw material in battery manufacturing. The construction of a battery manufacturing plant can have a positive impact on the country's economy, such as creating new jobs and improving technological capabilities and innovation in Indonesia, thereby enhancing the competitiveness of the national industry. This study uses primary and secondary data to analyse the requirements for designing an aesthetically pleasing, functional, and efficient battery manufacturing plant. The design of a battery manufacturing plant can produce a functional and efficient building design for the battery production process, as well as an ergonomic and comfortable interior design for workers, thereby improving productivity and workplace safety. Additionally, the design of a battery manufacturing plant can integrate natural lighting systems to reduce energy requirements and improve worker comfort. Thus, an effective battery manufacturing plant design not only enhances efficiency, safety, and product quality while reducing environmental impact and production costs but also improves functional aesthetic value.